Social Facts and Semantic Fields of the “Fourth Estate” Metaphor - Mihailova, Katia (Research Papers, 2021)
The “Fourth estate” is a 233-year-old metaphor that encodes the functions of the media and journalism in the process of social transformation or social dynamics, as Auguste Comte would put it. To be the spiritual engine of the transformation processes in a given society – this is the main responsibility of the “Fourth Estate” to this day. Whether it is up to its civic and moral responsibility is another matter.The current study does not offer an answer to this question. Its subject is the social facts and semantic fields of metaphor over the centuries of its existence and its use in political rhetoric, research and art – especially literature, cinema and television films.The object of the study is the metaphor “Fourth Estate” itself as one of the most persistent metaphors today. Despite its various applications over time, the metaphor continues to encode the same social facts – generally speaking, the media. The first uses of the methaphor relate to the social functions of the press. Then it accept radio and television and today there is a discussion about whether social media are social facts behind the metaphor of the “Fourth Estate” or they become facts of another metaphor – the “Fifth Estate”.The study presents a historical and theoretical overview of the development of the metaphor of the “Fourth Estate”. A content analysis of the works of art bearing the metaphor in its title has been made.